Penanganan berbagai Tingkat Kelengketan pada Alat gelas di Laboratorium dari Pengaruh Basa kuat Larutan NaOH beserta Ujinya - Sri Harjanto; Indra Gunawan (UPT Laboratorium Terpadu, Universitas Diponegoro, 2020)
As PLP (Educational Laboratory Institution) or other laboratory personnel for their daily work, they are very closely related to the tools and materials in the laboratory scope, and cannot be separated from laboratory equipment in the form of instruments or glassware. The problem here is that there are times when we encounter glassware in the scope of a laboratory whose faucet is closed or the faucet cannot be opened because it is sticky, and on average it is used after using NaOH base solution. That is why we are here to try to do a test to find out how much the stickiness of a device made from glass raw materials. By using variable various levels of concentration of NaOH solution with different time periods. As a decay the detergent solution is also used in various levels of concentration and heating. . From the data of the stickiness level test results using variable concentrations of NaOH solution and detergent solution will get the results that with the increasing concentration of NaOH solution, the stickiness will also be stronger. Likewise with the passage of time the longer the NaOH solution comes into contact with materials made of glass, the harder it will become and the stickiness will also be stronger so that it will be more difficult to be released. while on a strong adhesiveness will be more effective when using the immersion method at a temperature of 60-70 ° C.